Analisis Protein dan Energi pada MP-ASI campuran Tepung Beras, Pisang Awak dan Ikan Lele - Rohana Dewi Adriani; Jumirah .; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
The complimentary feeding can ensure the nutrient a baby requires in appropriate amounts for his growth and development. The complimentary feeding which is made of the mixed of rice flour, banana and catfish can fulfill baby’s nutrition need. The aim of this research is to measure the proteins and energy contents of rice powder, awak bananas and catfish as a mixed complimentary food. This is an experimental research on mixed complimentary feeding of rice flour, awak bananas, and catfish. Its protein content was determined by Kjedahl method and the energy content was determined by calculating the protein, fat and carbohidrate. The result of this research showed that mixed complimentary feeding of rice powder, awak bananas, and catfish as its, serves 17,9 gram of protein, 400,8 Kkal of energy. The characteristic of mixed complimentary food of rice flour, bananas, and catfish has spesific scent, sweet flavour and smooth texture. The mixed complimentary feeding of rice flour, bananas, and catfish as its ingredients and ready to eat meals has already met the standart made by Indonesian Health Department 2007which makes it adequate as a good complimentary feeding for a 6-12-month baby. It is sugested to feed this kind of complimentary feeding to a baby as it can complete 100% protein and 50% energy needs of babies. Keywords : Protein, energy, complementary food of breastfeeding, rice flour, banana, catfish.